Force-clamp spectroscopy identifies a catch bond mechanism in a Gram-positive pathogen - Marion Mathelié-Guinlet (Nature Portfolio, 2020)
During colonization of host tissues and biomaterials, staphylococci are exposed to extreme mechanical forces. Here authors use force-clamp spectroscopy and show that the dock, lock and latch interaction between staphylococcal surface protein SpsD and fibrinogen is extremely strong, and exhibits an unusual catch-slip transition.